The Leadership Influence on the Performance of Village-Owned Enterprise (BUMDesa) Employees of Lontar Sewu Gresik Regency - Adi Prasetyo, Ferdiansyah; Wibawani, Sri (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The aim of this research is to determine leadership influence on the performance of Village-Owned Enterprise (BUMDesa) Employees of Lontarsewu Gresik RegencyThe research used quantitative methods because it suits the purpose of this research, which aims to measure the leadership influence on the performance of BUMDesa Lontar Sewu employees, Hendrosari Village, Menganti District, Gresik Regency. Based on the results of processing, analysis, and discussion of research data, several points can be concluded as follows coefficient of determination value on the influence between leadership variables and employee performance is 0,55. Correlation coefficient value for the relationship between leadership variables and employee performance variables is 0,74 which interpreted as a strong level of relationship. It can be concluded that the better the leadership of the BUMDesa director, the better the performance of BUMDesa Lontar Sewu employees. The average value of the measurement components based on descriptive analysis of the leadership variable is 4,4 with a very successful interpretation; and the average value of the measurement component of the employee performance variable is 4,6 with a very high interpretation.